The cultural history reader - Marsden, Ben; McCaffery, Peter Gabriel (Routledge readers in history, 2014)
The Cultural History Reader is the first volume to collect together the distinctive contributions made by cultural historians across the spectrum of historiographical methods. It offers a unique view into the insights to be gained from examining how cultural factors have shaped people's experiences of the world and guided their actions. Featuring eleven thematic sections, covering everything from childhood to technology and war to popular culture, this book bridges disparate themes, periods, nationalities and religions to present detailed analyses of a variety of cultural responses and interpretations in diverse historical contexts. Peter McCaffery and Ben Marsden use their wealth of experience in teaching and researching cultural history to identify key topics and to provide the most telling extracts, illustrating how different social and cultural factors intersect and link together to give a richer picture of the past in all its surprising complexity. They also provide authoritative and clearly written introductions that contextualize each section and show the ways in which the themes have been handled by different cultural historians. The book provides a detailed and accessible introduction to cultural history as a discipline, outlining how it has developed since the eighteenth century and where it differs from related disciplines such as sociology, anthropology and archaeology. The Cultural History Reader is a perfect resource for all students of cultural history and all those interested in how focusing on cultural factors has shaped our understanding of the past.